Standard catalog of world coins, 1801-1900 - Bruce, Colin R.; Michael, Thomas (Iola, WI : Krause, 2006)
Contains detailed images of twentieth century coins from around the world, with information on market values, KM identification numbers, mintage figures, metallic and other compositions, and precious metal weights, and features coverage of coin issues.
Adult
Keywords: Coins -- Catalogs; Coins -- Collectors and collecting